2008
DOI: 10.1523/jneurosci.4458-07.2008
|View full text |Cite
|
Sign up to set email alerts
|

The Dysphoric Component of Stress Is Encoded by Activation of the Dynorphin κ-Opioid System

Abstract: Stress is a complex human experience having both positive and negative motivational properties. When chronic and uncontrollable, the adverse effects of stress on human health are considerable and yet poorly understood. Here, we report that the dysphoric properties of chronic stress are encoded by the endogenous opioid peptide dynorphin acting on specific stress-related neuronal circuits. Using different forms of stress presumed to evoke dysphoria in mice, we found that repeated forced swim and inescapable foot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
593
1
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 548 publications
(615 citation statements)
references
References 46 publications
17
593
1
4
Order By: Relevance
“…The relationship between the CRF, adrenergic, and dynorphin systems in stress-induced reinstatement has not been resolved; however, we recently reported that CRF-induced place aversion was mediated by dynorphin-dependent KOR activation (Land et al 2008). Several additional lines of evidence support a possible dynorphin-CRF interaction in mediating stressinduced reinstatement.…”
Section: Discussionmentioning
confidence: 97%
“…The relationship between the CRF, adrenergic, and dynorphin systems in stress-induced reinstatement has not been resolved; however, we recently reported that CRF-induced place aversion was mediated by dynorphin-dependent KOR activation (Land et al 2008). Several additional lines of evidence support a possible dynorphin-CRF interaction in mediating stressinduced reinstatement.…”
Section: Discussionmentioning
confidence: 97%
“…Stress increases the levels of dynorphin (Nabeshima et al, 1992;Land et al, 2008;Bruchas et al, 2010), which is an endogenous KOR ligand (Chavkin et al, 1982). Both repeated forced swim stress and pharmacological activation of KORs with U50,488 increases ethanol consumption in mice (Sperling et al, 2010;Rose et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…For example, the prototypical KOR antagonist nor-binaltorphimine (nor-BNI) blocks CRF-induced dysphoria in the place conditioning test (Land et al, 2008) and reductions in open arm time in the elevated plus maze (Bruchas et al, 2009). Our group has shown in preliminary tests that JDTic, another highly selective KOR antagonist that is structurally unrelated to nor-BNI (Carroll et al, 2004), also blocks CRF-induced elevations in acoustic startle behavior ( Van't Veer et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Our group has shown in preliminary tests that JDTic, another highly selective KOR antagonist that is structurally unrelated to nor-BNI (Carroll et al, 2004), also blocks CRF-induced elevations in acoustic startle behavior ( Van't Veer et al, 2011). The observations that CRF-induced phosphorylation of KORs is blocked by KOR antagonists (Land et al, 2008) and CRF-induced anxiety behavior is reduced in dynorphin knockout mice (Bruchas et al, 2009) provide molecular evidence for links between CRF and KOR systems. Interactions between these systems have been thoroughly characterized within the raphe nucleus (Bruchas et al, 2011) but may also occur in other brain regions (Pliakas et al, 2001;Newton et al, 2002;Shirayama et al, 2004;Muschamp et al, 2011b;Knoll et al, 2011).…”
Section: Introductionmentioning
confidence: 99%